Evaluation of Soft Tissue Regenerative Processes After Subcutaneous Implantation of Silver/ Poly(Vinyl Alcohol) and Novel Silver/Poly(Vinyl Alcohol)/Graphene Hydrogels in an Animal Model - Lužajić Božinovski, Tijana; Todorović, Vera; Milošević, Ivan; Gajdov, Vladimir; Prokić, Bogomir Bolka; Nešović, Katarina; Mišković-Stanković, Vesna; Marković, Danica (Acta veterinaria (Beograd), 2021)
A newly produced biomaterial is necessarily subject of standards, which are performed on animal models. For the evaluation of soft tissue regenerative possibilities after subcutaneous implantation of biomaterials – silver/poly(vinyl alcohol) (Ag/PVA) and novel silver/poly(vinyl alcohol)/graphene (Ag/PVA/Gr) provided for clinical use, sixteen rats were used, according to the instructions of international standards, ISO 10993-6, 2007. Histological sections were observed 7, 15, 30 and 60 days after grafting. These hydrogels were produced by electrochemical synthesis of silver nanoparticles in the polymer matrices, which enabled obtaining completely safe and biocompatible materials, free from any additional toxic chemical reducing agents. Surgical implantation of hydrogels was done according to the permission of the Ethical Committee of the Faculty of Veterinary Medicine, University of Belgrade. Immunohistochemical (IHC) studies included the assessment of smooth muscle expression actin in blood vessels (α-SMA), the expression of laminin and type I and type III collagen in the skin structures, and, the determination of cell proliferation marker expression (Ki-67) keratinocytes. The results were assessed in a semiquantitative manner. The data were analyzed in the statistical software package IBM SPSS 20. The conclusions indicated that Ag/PVA/Gr might be used as wound dressings to enhance the tissue healing potential and established faster integration and shorter retention in the tissue.